In vivo CAMPATH-1H prevents graft-versus-host disease following nonmyeloablative stem cell transplantation. - Kottaridis, P; Milligan, D; Chopra, R; Chakraverty, R; Chakrabarti, S; Robinson, S; Peggs, K; Verfuerth, S; Pettengell, R; Marsh, J; Schey, S; Mahendra, P; et al. (2000)
A novel nonmyeloablative conditioning regimen was investigated in 44 patients with hematologic malignancies. The median patient age was 41 years. Many of the patients had high-risk features, including 19 patients with a previous failed transplant. Recipient conditioning consisted of CAMPATH-1H, 20 mg/day on days -8 to -4; fludarabine, 30 mg/m(2) on days -7 to -3; and melphalan, 140 mg/m(2) on day -2. Thirty-six recipients received unmanipulated granculocyte colony-stimulating factor-mobilized peripheral blood stem cells from HLA-identical siblings, and 8 received unmanipulated marrow from matched unrelated donors. GVHD prophylaxis was with cyclosporine A alone for 38 patients and cyclosporine A plus methotrexate for 6 sibling recipients. Forty-two of the 43 evaluable patients had sustained engraftment. Results of chimerism analysis using microsatellite polymerase chain reaction indicate that 18 of 31 patients studied were full-donor chimeras while the other patients were mixed chimeras in one or more lineages. At a median follow-up of 9 months (range 3 to 29 months), 33 patients remain alive in complete remission or with no evidence of disease progression. Seven patients relapsed or progressed post-transplantation, and 4 of them subsequently died. Four patients died of regimen-related complications. There were no cases of grades III-IV acute GVHD. Only 2 patients developed grade II acute GVHD, and only 1 had chronic GVHD. The estimated probability of nonrelapse mortality was 11%. Although longer follow-up is needed to establish the long-term remission rates, this study demonstrates that this nonmyeloablative preparative regimen is associated with durable engraftment, minimal toxicity, and low incidence of GVHD.